Does Capital Account Liberalization Affect Income Inequality? - Xiang Li; Dan Su (Oxford Bulletin of Economics and Statistics, 2021)
By adopting an identification strategy of difference-in-difference estimation combined with propensity score matching between liberalized and closed countries, this paper provides robust evidence that opening the capital account is associated with an increase in income inequality in developing countries. Specifically, capital account liberalization, in the long run, is associated with a reduction in the income share of the poorest half by 2.66–3.79% points and an increase in that of the richest 10% by 5.19–8.76% points. Moreover, directions and categories of capital account liberalization matter. The relationship is more pronounced when liberalizing inward and equity capital flows.
Keywords: 330